Penggunaan Sumber Belajar Berbasis Information Technologi dalam Meningkatkan Hasil Belajar Siswa Pelajaran IPS di Kelas VIII MTs Nuris Silo - Fikriatul Hasanah (Institut Agama Islam Negeri Jember, 2021)
The use of learning resources in the teaching and learning process is very necessary for both teachers and students. Learning resources are all kinds of sources that exist outside of students whose existence facilitates the learning process. Information technology is defined as science in the field of computer-based information and its development is very rapid. In the world of education, the existence of information technology as a medium is very necessary. Teachers can use learning resources obtained from the internet in the form of ebooks, journals and others so that students' insights can be broadened. MTs Nuris Silo in the learning process, the teacher uses Information Technology-based learning resources in Social Studies Subjects for class VIII, namely the teacher uses student books in the form of ebooks, uses videos, articles from the internet, and pictures. The results of the use of technology-based learning resources can facilitate the learning process. students understand what is explained by the teacher from those who do not know to know, from those who do not understand to understand. Learning outcomes are an important aspect for educators, because by assessing student learning outcomes, educators obtain information about student learning progress. This has been proven by the results of the assignments given by the teacher.